Prove that: sin2
(n +1) A - sin2 nA = sin (2n + 1) A sin A.
Answers
Answered by
1
Step-by-step explanation:
please mark me as brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d2b/5082c4ae6865ab84943a33aaf26f33d0.jpg)
Answered by
0
Answer:
sin2(n+1)A - sin2nA = sin(2n+1)A.sinA
we have formula sin2a - sin2b =sin(a-b)sin(a+b)
therefore
sin2(n+1)A - sin2nA=sin[(n+1)A+nA].sin[(n+1)A-nA]
=sin(2n+1)A.sinA =RHS
hence proved
Similar questions
English,
2 months ago
English,
4 months ago
Social Sciences,
4 months ago
Math,
11 months ago
Math,
11 months ago